(untitled) (Sebha University Conference Proceedings, 2024)
Due to the unstable situation in certain oil-producing nations, Oil and petrochemical production is projected to decrease so that the option to abandon a plant and temporary shutdown will increase. Therefore, the comprehensive method from the pre-mothballing, mothballing, and recommissioning stages should be developed. Corrosion in refineries is a critical issue affecting various units, necessitating preventive measures such as cathode protection, inhibitors, and protective coatings. Exploring the strategies and methods used for maintaining and preserving oil refinery and petrochemical plants during periods of inactivity to prevent corrosion issues is a crucial. Oil refinery and petrochemical plants are susceptible to corrosion, which can have detrimental effects on their equipment and overall performance. By implementing effective mothballing techniques, such as surface preparation, the use of protective coatings and inhibitors, and adequate storage and monitoring practices, corrosion can be mitigated. This work provides a comprehensive understanding of mothballing methods essential for the longevity and optimal functioning of oil refinery and petrochemical plants.